Dynamical System Analysis and Optimal Control Measures of Lassa Fever Disease Model - Ifeanyi Sunday Onah; Obiora Cornelius Collins; Praise-God Uchechukwu Madueme; Godwin Christopher Ezike Mbah (International Journal of Mathematics and Mathematical Sciences)
Lassa fever is an animal-borne acute viral illness caused by the Lassa virus. This disease is endemic in parts of West Africa including Benin, Ghana, Guinea, Liberia, Mali, Sierra Leone, and Nigeria. We formulate a mathematical model for Lassa fever disease transmission under the assumption of a homogeneously mixed population. We highlighted the basic factors influencing the transmission of Lassa fever and also determined and analyzed the important mathematical features of the model. We extended the model by introducing various control intervention measures, like external protection, isolation, treatment, and rodent control. The extended model was analyzed and compared with the basic model by appropriate qualitative analysis and numerical simulation approach. We invoked the optimal control theory so as to determine how to reduce the spread of the disease with minimum cost.